Implementation of Smartphone Media on Information Search Strategy in PAI Learning Class XI SMA Negeri 1 Pangkalpinang - Rahman, Priyanggo Karunia; Harvina, Kurnia (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The observations for this problem were conducted in class XI of SMA Negeri 1 Pangkalpinang. Contemporary educators continue to employ conventional instructional methods in the present day. Due to a lack of alignment between educators' tactics and the information being taught, students encounter difficulties in comprehending the subject matter. This paper addresses two issues: (1) optimizing the utilization of smartphone media for information retrieval strategies in PAI learning among XI grade students at SMA Negeri 1 Pangkalpinang; and (2) identifying the factors that impede the effective use of smartphone media for information retrieval strategies in PAI learning among XI grade students at SMA Negeri 1 Pangkalpinang. This qualitative research methodology entailed conducting interviews with the principal, teachers specializing in PAI, and grade XI students at SMA Negeri 1 Pangkalpinang. The study also investigated the utilization of smartphone media to optimize the implementation of information-seeking strategies in PAI learning for 11th-grade students. The study also employed pertinent data and papers. The findings indicated that utilizing cellphones to optimize knowledge retrieval strategies in PAI learning at SMA Negeri 1 Pangkalpinang proved to be a viable approach for instructors to develop learning strategies that align with students' expectations. Nevertheless, students frequently misuse smartphones, particularly by developing an addiction to gaming and perhaps failing to utilize them appropriately.